Electron transfer process in microbial electrochemical technologies: The role of cell-surface exposed conductive proteins. (May 2018) - Costa, Nazua L.; Clarke, Thomas A.; Philipp, Laura-Alina; Gescher, Johannes; Louro, Ricardo O.; Paquete, Catarina M.
Highlights: Electroactive organisms in MET perform extracellular electron transfer processes. Extracellular electron transfer relies on cell-surface exposed conductive proteins. There are 4 groups of cell-surface conductive proteins in electroactive organisms. Most electroactive organisms support their activity with multiheme cytochromes. Abstract: Electroactive microorganisms have attracted significant interest for the development of novel biotechnological systems of low ecological footprint. These can be used for the sustainable production of energy, bioremediation of metal-contaminated environments and production of added-value products. Currently, almost 100 microorganisms from the Bacterial and Archaeal domains are considered electroactive, given their ability to efficiently interact with electrodes in microbial electrochemical technologies. Cell-surface exposed conductive proteins are key players in the electron transfer between cells and electrodes. Interestingly, it seems that among the electroactive organisms identified so far, these cell-surface proteins fall into one of four groups. In this review, the different types of cell-surface conductive proteins found in electroactive organisms will be overviewed, focusing on their structural and functional properties.